Karakteristik Batubara Formasi Sinjin di Daerah Siduung Kecamatan Segah Kabupaten Berau Kalimantan Timur - Wahyu Sugiarto; Andy Erwin Wijaya (Retii, 2022)
The Sinjin Formation is one of the formations found in the Berau Sub Basin which has the potential for coal. This research aims to identify the presence of coal in the Sinjin Formation by using geological mapping methods, drilling and coal qualitative analysis. By geological mapping found 6 coal outcrops with a thickness ranging from 0.08 to Â± 1 meter, and 8 non-coal outcrops, namely claystone, sandstone and limestone. There were 14 drill points carried out in the research area. The quality of coal in the Sinjin Formation is indicated by the mean value of Total Moisture 48.3%, Inherent Moisture 16.3%, Ash Content 5.9%, Volatile Matter 39 ,8 %, Fixed Carbon 38,1 %, Sulfur Content (Total Sulphur) 0,06 %, and Calorific Value 5236 Kcal/kg (adb).